From gene expression to serum proteins: biomarker discovery in ankylosing spondylitis - Haroon, N; Tsui, F W L; O’Shea, F D; Chiu, B; Tsui, H W; Zhang, H; Marshall, K W; Inman, R D (Annals of the rheumatic diseases, 2010)
Objectives:Studying post-infliximab gene expression changes could provide insights into the pathogenesis of ankylosing spondylitis (AS).Methods:Gene expression changes were screened by microarray on peripheral blood RNA of 16 AS patients at baseline and 2 weeks post-infliximab, and selected results were confirmed by quantitative real-time (qRT)–PCR. Corresponding serum-soluble LIGHT (sLIGHT) was estimated by ELISA and the fold change in sLIGHT was correlated to the fold change in erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and the Bath AS disease activity index.Results:Post-infliximab, 69% of the patients (11/16) achieved an ASAS20 response. Six candidate genes were differentially expressed by microarray; four of which were validated by qRT–PCR. sLIGHT showed the most significant difference. There was good correlation of baseline sLIGHT with CRP (R  =  0.60; p = 0.01) and ESR (R  =  0.51; p = 0.04). The fold change in sLIGHT correlated with change in both CRP (R  =  0.71, p = 0.002) and ESR (R  =  0.77, p<0.001).Conclusion:LIGHT is significantly downregulated by infliximab. sLIGHT correlated well with changes in inflammatory markers.